2015
DOI: 10.1002/zaac.201400531
|View full text |Cite
|
Sign up to set email alerts
|

Green Luminescence of Divalent Europium in the Hydride Chloride EuHCl

Abstract: Abstract. Luminescence properties of divalent europium in the mixedanion hydride chloride EuHCl were studied for the first time. Olivegreen single crystals of EuHCl (PbFCl-type structure: tetragonal, P4/nmm, a = 406.58(3) pm, c = 693.12(5) pm, c/a = 1.705, Z = 2) resulted from the reaction of elemental europium (Eu), sodium hydride (NaH) and sodium chloride (NaCl), while powder samples were prepared from the binary components europium dihydride (EuH 2 ) and dichloride (EuCl 2 ). Low temperature X-ray powder di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…In the hydride chloride of divalent europium, EuHCl, crystallizing in the matlockite‐type structure (space group P 4/ nmm ), green broad band luminescence (maximum 510 nm) was observed . The europium cation is located inside a square antiprism formed by four hydride and five chloride anions and capped by one of the five chloride anions .…”
Section: Eu2+‐doped Hydridesmentioning
confidence: 99%
“…In the hydride chloride of divalent europium, EuHCl, crystallizing in the matlockite‐type structure (space group P 4/ nmm ), green broad band luminescence (maximum 510 nm) was observed . The europium cation is located inside a square antiprism formed by four hydride and five chloride anions and capped by one of the five chloride anions .…”
Section: Eu2+‐doped Hydridesmentioning
confidence: 99%
“…For the past decades, hydrides and mixed anion hydrides containing Eu 2+ dopant have been reported to exhibit green-red luminescence. 10,[14][15][16][17][18][19][20] However, their poor stability in air and moisture limits their application. In contrast, we have recently demonstrated that oxyhydride GdHO is stable in ambient air and can act as a phosphor host for Tb 3+ .…”
Section: Introductionmentioning
confidence: 99%
“…For such broad 5d–4f emission spectra, it is, even at low temperatures, rare that a well-resolved vibrational fine structure showing coupling to several modes can be observed because the coupling strength is usually intermediate; that is, the Huang–Rhys parameter S has the value 1 < S < 5 . However, some rare examples exist for Ce 3+ , Pr 3+ , and Tb 3+ with well-resolved spectra that show a coupling to two vibrations in double perovskites. Recently, new types of host materials, ionic hydrides, complex hydrides, , and mixed anionic compounds containing hydrides, have been studied as hosts for Eu 2+ luminescence. Here, it was found that replacing less polarizable anions by the polarizable hydride anion can lead to wide shifts of the barycenter of the 5d levels to lower energies.…”
Section: Introductionmentioning
confidence: 99%